A Systematic Literature Review of Canva-Assisted Interactive Learning Media Development in Elementary School Mathematics (2021–2026) - Mukti Hariyadi; Ardhi Prabowo; Decky Avrilianda; Nuni Widiarti (Program Studi Pendididikan Guru Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2026)
This study aims to analyze the development of Canva-assisted interactive learning media in elementary school mathematics through a Systematic Literature Review (SLR) approach. The review was conducted on 10 selected articles published between 2021 and 2026. The articles were selected based on the following criteria: relevance to elementary school mathematics learning, discussion of Canva-assisted media, open-access availability, and valid DOI registration. The article search and selection process followed the PRISMA 2020 guidelines. The data were analyzed descriptively by examining the development models, media formats, mathematics topics, as well as the validity and practicality of the developed media. The findings indicate that Canva-based media were developed in various forms, including digital storybooks, student worksheets, interactive quizzes, e-booklets, and other digital learning media. The topics addressed included data processing, simple fractions, geometry, solid figures, and numbers. In general, all studies reported that the developed media fell into the valid to highly valid category and were practical for use by both teachers and students. These findings confirm that Canva functions not only as a design tool but also as a pedagogical medium with the potential to help students understand mathematical concepts in a more concrete, engaging, and meaningful way.